2001
DOI: 10.1111/j.1530-0277.2001.tb02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Alcoholism and Toddler Noncompliance

Abstract: Background-This study examined the effect of fathers' alcoholism and associated risk factors on toddler compliance with parental directives at 18 and 24 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 62 publications
0
20
1
Order By: Relevance
“…There is evidence that parents treat boys and girls differently when it comes to discipline, although results have been inconsistent. Some studies found that parents showed similar levels of observed discipline behavior to boys and girls (Bernstein, Harris, Long, Iida, & Hans, 2005;Eddy et al, 2001;Russel & Russel, 1996) whereas others found evidence for differences in parental discipline toward boys and girls, with more coercion and control toward boys than girls (Das Eiden et al, 2001;Tam & Lam, 2003), but also more demandingness toward girls than boys (Das Eiden et al, 2001;Domenech Rodr ıguez et al, 2009). These inconsistencies could be due to methodological differences, as studies differed with respect to age and ethnicity of the children and the procedures to code parental discipline.…”
Section: Role Of Child Gendermentioning
confidence: 99%
“…There is evidence that parents treat boys and girls differently when it comes to discipline, although results have been inconsistent. Some studies found that parents showed similar levels of observed discipline behavior to boys and girls (Bernstein, Harris, Long, Iida, & Hans, 2005;Eddy et al, 2001;Russel & Russel, 1996) whereas others found evidence for differences in parental discipline toward boys and girls, with more coercion and control toward boys than girls (Das Eiden et al, 2001;Tam & Lam, 2003), but also more demandingness toward girls than boys (Das Eiden et al, 2001;Domenech Rodr ıguez et al, 2009). These inconsistencies could be due to methodological differences, as studies differed with respect to age and ethnicity of the children and the procedures to code parental discipline.…”
Section: Role Of Child Gendermentioning
confidence: 99%
“…Developmental outcomes exhibited in young childhood that are well‐established precursors of adolescent ATOD abuse include externalizing (eg, oppositional defiant disorder, conduct disorder, attention deficit hyperactivity disorder) and internalizing (anxiety, depression) disturbances 59 . One manifestation of behavioral undercontrol is non‐compliance with adult social expectations; this characteristic has been documented in sons (but not daughters) of alcoholic men 60 . Non‐compliance presages development of an oppositional defiant disorder which in turn consolidates an adjustment style that is featured by conduct problems and rebelliousness.…”
Section: Factors Associated With the Liability For Sudmentioning
confidence: 99%
“…For example, it is clear that mother's heavy alcohol use during pregnancy can lead to fetal alcohol spectrum disorders (Grant, Huggins, Connor, & Streissguth, 2005;Streissguth, 2001; for review, see e.g., Larkby & Day, 1997;Mattson & Riley, 1998), reflecting a range of physical, behavioral, and cognitive problems. Moreover, studies of the consequences of parental postnatal alcohol abuse and dependence have shown it to be associated with a host of developmental difficulties in young children, including insecure attachment in infancy (Eiden, Edwards, & Leonard, 2002), lower behavioral adjustment in toddlers (Eiden, Leonard, & Morrisey, 2001), self-regulation problems (Eiden, Edwards, & Leonard, 2004), and behavior problems in early childhood (Edwards, Leonard, & Das Eiden, 2001).…”
mentioning
confidence: 99%